The efficacy of guided growth as an initial strategy for Blount disease treatment. (August 2020) - Danino, Barry; Rödl, Robert; Herzenberg, John E.; Shabtai, Lior; Grill, Franz; Narayanan, Unni; Gigi, Roy; Segev, Eitan; Wientroub, Shlomo
Abstract: Purpose: The aim of this study was to evaluate the success of guided growth by temporal hemiepiphysiodesis of the lateral proximal tibia as a first line treatment option for Blount disease. Methods: This was a retrospective multicentre study conducted in five centres, covering data on 55 limbs in 45 patients, with an average follow-up of 24.5 months following plate insertion. Preoperative alignment analysis was compared with three measurements taken postoperatively. The normalization of the mechanical medial proximal tibia angle (mMPTA) was defined as the primary outcome measure. Results: Mean age at surgery was 9.5 years. Average preoperative mMPTA was 77°. On average, at 24.5 months post-surgery, mMPTA was 86.33°, while 43/55 limbs (78.18%) have achieved normalization (mMPTA 85° to 90°). Average rate of correction was 1° per month. When grouping the children as infantile (11 limbs), juvenile (12 limbs) and adolescent (32 limbs), operated on before the age of four years, between four and ten years and after the age of ten years, respectively, 63.63%, 66.67%, 87.5% have completed correction of deformity during the follow-up period. Interestingly, the femoral component of the deformity has achieved correction as well in 33/55 limbs (64%). Conclusion: Hemiepiphysiodesis is an effective first line treatment for Blount disease. Overall success rate is good but varies according to child's age. Adolescent Blount has the best chance of achieving full correction while same treatment is less effective in infantile Blount. Level of evidence: IV